Guinea : Sixth and Seventh Reviews under the Extended Credit Facility Arrangement, Financing Assurances Review, and Requests for Waivers of Nonobservance of Performance Criteria, Extension of the Arrangement, and Rephasing of Disbursements-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report, 2016)
This report reviews Guinea's economic performance under the program supported by an Extended Credit Facility (ECF) arrangement. Guinea was declared free of the Ebola epidemic at end-2015, and after two years of stagnant activity, growth is expected to rebound this year. After solid performance in 2014, ECF program implementation weakened in 2015. Following last October's Presidential elections, there has been a concerted effort to bring the ECF-supported program back on-track. Macroeconomic policies for 2016 aim to improve reserves coverage to three months of imports, and keep inflation within single digit figures as envisioned in the 2015 ECF-supported program. The 2016 budget envisions a significant broad-based fiscal contraction.